Náležitosti směnek - Václavíková, Kateřina; Kotásek, Josef, 1973-; Masarykova univerzita. Katedra obchodního práva (2006)
Essentials of Bill of Exchange and Promissory Note are mentioned and followed as per Exchange and Cheques law No. 191/1950 and law No. 29/2000.
Vedoucí práce: Josef Kotásek.
Bakalářská práce (Bc.)--Masarykova univerzita, Právnická fakulta, 2006.
Keywords: směnky; bills of exchange; bakalářské práce